(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Education plays a crucial role in the overall development and prosperity of a nation. It is widely regarded as an essential determination of social, economic, and human development. In a diverse country like India, with its vast population and regional disparities, understanding the variation in education indices across different states is of utmost importance. This paper studies the econometric analysis of the variation in education index across Indian states in 2021. This paper attempts determine if the education infrastructure index and NSDP Per capita can lead to the variations in the education index across Indian states. It also attempts to know whether the nature of the states can influence the variations across the states.